Comparative Study of Size, Total Protein, Fibrinogen and 5-HT Content of Human and Canine Platelet Density Subpopulations - Mezzano, Diego; Aranda, Eduardo; Foradori, Arnaldo (Thrombosis and Haemostasis, 1986)
The size, total protein, fibrinogen and 5-HT content were evaluated in density subpopulations of human and canine platelets fractionated in linear arabinogalactan gradients. The methodology was assessed to ascertain that platelet separation was by density and to discard artifactual changes and platelet release during the procedure. EDTA or PGEi increased the size of human PRP-platelets, but not of dog platelets. In humans, high density (HD) platelets were 1.26 times larger and contained 1.88 times more fibrinogen, 2.23 times more 5-HT and 1.37 times more protein than low density (LD) platelets; in dogs, these density cohorts did not differ in protein content, but LD platelets were 1.29 times larger and had 1.33 times more fibrinogen and 5-HT than HD platelets. These findings suggest that cell density is mostly dependent on the protein content per unit volume of platelets (and not on dense bodies). The differences in fibrinogen and 5-HT content between HD and LD cohorts in humans and dogs may be related to platelet age. The difference in volume between HD and LD platelets in dogs is of uncertain interpretation.
Keywords: Platelet density; Size; Fibrinogen; 5-HT; Age